2021
DOI: 10.1016/j.susc.2020.121796
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization of the honeycomb structure of zinc antimonide (ZnSb) monolayer: A first-Principles study

Abstract: Structural, electronic, optic and vibrational properties of Zinc antimonide (ZnSb) monolayers and their functionalized (semifluorinated and fully chlorinated) structures are investigated by means of the first-principles calculations. The phonon dispersion curves reveal the presence of imaginary frequencies and thus confirm the dynamical instability of ZnSb monolayer. The calculated electronic band structure corroborates the metallic character with fully-relativistic calculations. Moreover, we analyze the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 55 publications
1
6
1
Order By: Relevance
“…It exhibits a nearly direct band gap of 0.38 eV with the conduction band minimum (CBM) at the Γ point and the valence band maximum (VBM) slightly away from the Γ point. This gap value is smaller than 0.5 eV reported by Bafekry et al , 41 which could be due to the consideration of spin–orbit coupling. The orbital-projected density of states show that the conduction band states near Fermi level are mainly composed of the Sb-p and Cl-p orbitals, indicating a strong orbital interaction.…”
Section: Resultscontrasting
confidence: 57%
“…It exhibits a nearly direct band gap of 0.38 eV with the conduction band minimum (CBM) at the Γ point and the valence band maximum (VBM) slightly away from the Γ point. This gap value is smaller than 0.5 eV reported by Bafekry et al , 41 which could be due to the consideration of spin–orbit coupling. The orbital-projected density of states show that the conduction band states near Fermi level are mainly composed of the Sb-p and Cl-p orbitals, indicating a strong orbital interaction.…”
Section: Resultscontrasting
confidence: 57%
“…Defects can play different roles such as carrier donors, scattering, trapping, and recombination centers [36][37][38][39]. Furthermore, the properties of the 2DMs can be tailored via defect engineering [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…But, DFT study of the CsPbCl 3 monolayer showed that it consists of a wide bandgap which limits its solar cell applications; hence, we thought of opting for some alternative technique which in turn would enhance the properties of the monolayer and further our cause. For modifying various properties of the monolayer, techniques such as doping, strain engineering, applying an electric field, and many other methods are being practiced. Here we opted for the technique of adding impurities (Mn and Nb) into our monolayer which might lead to certain modifications in its electronic properties. Even though Mn doping is highly studied, , the reason behind considering Mn as dopant is its ability to induce optical properties in the doped host semiconductor nanocrystals.…”
mentioning
confidence: 99%